2011
DOI: 10.1093/jjco/hyr105
|View full text |Cite
|
Sign up to set email alerts
|

Post-marketing Surveillance (PMS) of all Patients Treated with Irinotecan in Japan: Clinical Experience and ADR Profile of 13 935 Patients

Abstract: It was reconfirmed that the incidences of serious leukopenia, thrombocytopenia and diarrhea were high among the patients with contraindication or careful administration of its use prescribed in the drug package insert. Therefore, for proper use of irinotecan, it is important to discriminate the patient on the basis of risk status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In patients with ovarian cancer, mitomycin C, which is effective for clear-cell carcinoma, was concomitantly used in 30% of patients. On the other hand, in patients with colorectal cancer, of whom 51% received irinotecan monotherapy, the incidence of severe adverse drug reactions was lower than that of patients with lung cancer and ovarian cancer (5). Therefore, it was suggested that predictive factors of adverse drug reactions of irinotecan may depend on the dose and regimen as well as concomitant anticancer drug used.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In patients with ovarian cancer, mitomycin C, which is effective for clear-cell carcinoma, was concomitantly used in 30% of patients. On the other hand, in patients with colorectal cancer, of whom 51% received irinotecan monotherapy, the incidence of severe adverse drug reactions was lower than that of patients with lung cancer and ovarian cancer (5). Therefore, it was suggested that predictive factors of adverse drug reactions of irinotecan may depend on the dose and regimen as well as concomitant anticancer drug used.…”
Section: Discussionmentioning
confidence: 96%
“…A previous article has already reported the practical method of this survey in detail (5). In brief, patients were enrolled by a central registration method before treatment with irinotecan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further research is warranted in mechanism of CID and targeted strategies like bacterial β-glucuronidase inhibition, individualized therapy based on genotyping and intratumoral drug activation. Also careful management of polypharmacy [210] and proper use of CPT-11 in only indicated situations [211] can help in bringing down incidence of CID.…”
Section: Discussionmentioning
confidence: 99%
“…In liver, active SN-38 is metabolised into its inactive β-glucuronide form (SN-38G) by uridine-diphosphate glucuronosyltransferase (UGT) 89 . For the first time, irinotecan was approved in 1994 in Japan for the treatment of SCLC and non-small cell lung cancer (NSCLC), ovarian cancer and cervix cancer 90 . Marketed by Pfizer Inc. and known as Camptosar® it is used for the treatment of colorectal cancer 91 .…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%